Seychelles : Sixth Review Under the Extended Arrangement and Request for an Extension of the Arrangement and Augmentation of Access-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report, 2013)
Resilient growth is observed in 2012 in Seychelles. Weakness in tourism has been offset by increases from less-traditional markets. The current account and adjustments has administered prices in the second half of 2011, and a cycle of depreciation and inflation ensued. The fiscal accounts suffered in the first half of 2012 from the restructuring arrangement for Air Seychelles. The banking system remains solid and continues to maintain healthy capital adequacy ratios. Despite strong program performance, Seychelles remains highly vulnerable to external shocks.